2017
DOI: 10.1016/j.jssr.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Teaching with the C3 Framework: Surveying Teachers' Beliefs and Practices

Abstract: The C3 Framework encourages ambitious inquiry-based social studies teaching. While inquiry is regularly recommended as a preferred pedagogy, research has shown that social studies teachers rarely engage students in inquiry. This exploratory study surveyed social studies teachers in one school district in a southeastern state to update our understanding of teachers’ instructional beliefs and practices related to inquiry and the C3 Framework. Survey responses were analyzed using descriptive statistics and open c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 30 publications
0
15
0
1
Order By: Relevance
“…In K-12 social studies classrooms, researchers have found that despite the field’s support of inquiry-oriented curriculum, the approach is uncommonly implemented (e.g. Saye et al , 2009; Thacker et al , 2017). Citing the lack of models for teaching through inquiry, Saye et al (2009, p. 7) lament the difficulty of changing teachers’ instructional practices toward inquiry.…”
Section: Introductionmentioning
confidence: 99%
“…In K-12 social studies classrooms, researchers have found that despite the field’s support of inquiry-oriented curriculum, the approach is uncommonly implemented (e.g. Saye et al , 2009; Thacker et al , 2017). Citing the lack of models for teaching through inquiry, Saye et al (2009, p. 7) lament the difficulty of changing teachers’ instructional practices toward inquiry.…”
Section: Introductionmentioning
confidence: 99%
“…The College, Career and Civic Life (C3) Framework (NCSS, 2013) promotes inquiry-oriented teaching and learning in the social studies (Grant, 2013;Grant et al, 2017a). While there is research demonstrating the efficacy of the inquiry design model (IDM) of the C3 Framework (Journell et al, 2018;Thacker and Friedman, 2017;Thacker et al, 2016), these studies have not engaged social studies teachers as coresearchers. In order to address this gap between theory and practice, we must learn more about practitioners' experiences and the factors that support or hinder inquiry-based instruction.…”
mentioning
confidence: 99%
“…Research suggests that these shifts in practice can be "challenging and frustrating" for teachers (Thacker and Friedman, 2017, p. 372).According to Saye (2017), to this point "Inquiry has been much more commonly advocated than realized in the [social studies] classroom" (p. 336). For example, teachers have reported difficulties associated with sourcing and content knowledge (Journell et al, 2018;Thacker and Friedman, 2017) as well as high-stakes tests (Thacker et al, 2016). This suggests the need for more specific guidance for social studies teachers to better enable them to integrate the C3 Framework into their teaching practice.…”
mentioning
confidence: 99%
“…Various studies have found that sustained and rigorous disciplinary inquiry is underused in social studies classrooms (Hicks, Doolittle & Lee, 2004) and teachers have different instructional beliefs and practices related to inquiry (Thacker, Lee & Friedman, 2016). Furthermore, teachers' epistemological assumptions and teaching dispositions can affect how they engage students in disciplined inquiry (Saye & Brush, 2006).…”
Section: Tools Of Historical Inquiry Practicesmentioning
confidence: 99%
“…While a recent survey has shown that teachers self-reported beliefs and practices somewhat align with the inquiry-centered practices promoted in the C3, the survey also found contradictions among their inquiry related beliefs and practices. For example, 76% of teachers reported using inquiry on a daily basis while only 18% of them reported inquiry as their most valued instructional practice (Thacker, Lee & Friedman, 2016). The scholars who published that survey data called for qualitative research to examine how teachers use inquiry and other practices aligned with the C3 in their classrooms.…”
Section: Introductionmentioning
confidence: 99%